Cytotoxicity of Particulate Matter PM10 Samples from Ouagadougou, Burkina Faso. (21st October 2022) - Guissou, Joelle Nicole; Baudrimont, Isabelle; Ouattara, Abdoul Karim; Simpore, Jacques; Sakande, Jean
Abstract : Particulate matter (PM) is one of the main air pollutants with 257, 000 deaths per year in Africa. Studying their toxic mechanisms of action could provide a better understanding of their effects on the population health. The objective of this study was to describe the PM10 toxic mechanism of action collected in 3 districts of Ouagadougou. Once per month and per site between November 2015 and February 2016, PM10 was sampled for 24 hours using the MiniVol TAS (AirMetrics, Eugene, USA). The collected filters were then stored in Petri dishes at room temperature for in vitro toxicological studies using human pulmonary artery endothelial cells (HPAEC) at the Bordeaux INSERM-U1045 Cardio-thoracic Research Center. The three study districts were classified based on PM10 level (high, intermediate, and low, respectively, for districts 2, 3, and 4). PM10 induced a concentration-dependent decrease in cell viability. A significant decrease in cell viability was observed at 1 µ g/cm 2, 10 µ g/cm 2, and 25 µ g/cm 2 for, respectively, districts 2, 3, and 4. A significant increase in the production of reactive oxygen species (ROS) was observed at 10 µ g/cm 2 for district 2 versus 5 µ g/cm 2 and 1 µ g/cm 2 for districts 3 and 4, respectively. Finally, a significant production of IL-6 was recorded from 5 µ g/cm 2 for district 4 versus 10 µ g/cm 2 for districts 2 and 3. Consequently, Ouagadougou is subjected to PM10 pollution, which can induce a significant production of ROS and IL-6 to cause adverse effects on the health of the population.